Unrestricted Gibonacci Hybrid Numbers - Bi̇lgi̇ci̇, Göksal (Matematikçiler Derneği, 2020)
Gibonacci sequence is a generalization of Fibonacci sequence and hybrid numbers are a mixture of reals, complex, dual and hyperbolic numbers. In this study, we introduce unrestricted Gibonacci hybrid numbers. After giving the definition of unrestricted gibonacci hybrid numbers, we give Binet--like formula for this kind of numbers. We also obtain some identities for unrestricted Gibonacci hybrid numbers.
Keywords: Matematik; Fibonacci numbers; gibonacci numbers; hybrid numbers; Mathematical Sciences